On the way into aerospace international integration - Бабак, В. П. (Proceedings of National Aviation University (archive), 2000)
Determined are the priority scientific directions which would allow to accelerate research integration of Ukrainian aerospace branch into international technological megapolicy. It is shown that scientific achievements of Kyiv International University of Civil Aviation in perfection of aerospace and information technologies will allow in the nearest future to take one of the leading places in the world